UJI VIABILITAS BAKTERI ASAM LAKTAT DARI USUS YANG DIPREPARASI DALAM RANSUM UNGGAS - Rudy Sutrisna; C.N. Ekowati; Salman Farisi; Hendra Verry Setyawan (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2017)
The aim of this study is to know the viability of Lactic Acid Bacteria isolates on ration and combination of ration with molasses. This study used a mixture of lactic acid bacteria isolates from the duck intestine (B4, B7, B8). The third bacterial isolates were inoculated on two different treatment media, on rantion media (R1), and combination of rantion + molasses (R2). The study was arranged by randomized block design (RAK) 6x2 factorial treatment pattern. Factor A is the incubation time of 0 hours, 2 hours, 4 hours, 6 hours, 8 hours and 10 hours. Factor B is two types of growing media of lactic acid bacteria, is ransum media, and combination of ransum + molasses. Each treatment was repeated 3 times. This research uses pour plate method with the calculation of the colony using colony counter. Data analyzed descriptively. The results showed that the addition of 1.6% molasses (R2) maintains the number of LAB population at 4th hour with the cell number 7,36 x 105 CFU / g. While on the ration medium (R1) can maintain the amount of LAB at 6th hour with the cell number of 6,20 x 105 CFU / g. LAB population viability on feed medium with addition of molases 1.6% (R2) has increased on storage time at 4th hour with cell number 7,36 x 105 CFU / g, while on feed medium (R1) decreased cell count 6,08 x 105 CFU / g. Keywords: Viability, Lactic Acid Bacteria, Ransum, Molase.